Effects of aspirin on dementia and cognitive function in diabetic patients: the ASCEND trial. (8th April 2022) - Parish, Sarah; Mafham, Marion; Offer, Alison; Barton, Jill; Wallendszus, Karl; Stevens, William; Buck, Georgina; Haynes, Richard; Collins, Rory; Bowman, Louise; Armitage, Jane
Abstract: Aims: Aspirin is widely used in cardiovascular disease prevention but is also associated with an increased risk of bleeding. The net effect of aspirin on dementia and cognitive impairment is uncertain. Methods and results: In the ASCEND trial, 15 480 people from the UK with diabetes and no history of cardiovascular disease were randomized to aspirin 100 mg daily or matching placebo for a mean of 7.4 years. The 15 427 ASCEND participants with no recorded dementia prior to baseline were included in this cognitive study with a primary pre-specified outcome of 'broad dementia', comprising dementia, cognitive impairment, or confusion. This was ascertained through participant, carer, or general practitioner report or hospital admission diagnosis, by 31 March 2019 (∼2 years beyond the scheduled treatment period). The broad dementia outcome occurred in a similar percentage of participants in the aspirin group and placebo group: 548 participants (7.1%) vs. 598 (7.8%), rate ratio 0.91 [95% confidence interval (CI), 0.81–1.02]. Thus, the CI excluded proportional hazards of >2% and proportional benefits of >19%. Conclusion: Aspirin does not have a large proportional effect on the risk of dementia. Trials or meta-analyses with larger total numbers of incident dementia cases to increase statistical power are needed to assess whether any modest proportional 10–15% benefits of 5–7 years of aspirin use on dementia exist. Clinical Trial Registration: Current Controlled Trials number, ISRCTN60635500; ClinicalTrials.gov number: NCT00135226. Structured Graphical Abstract: Structured Graphical Abstract The effect of aspirin on dementia in the ASCEND trial: Study design and summary results.